The Impact of Bariatric Surgery on Bone Health: State of the Art and New Recognized Links - Mendonça, Fernando; Soares, Raquel; Carvalho, Davide; Freitas, Paula (Hormone and Metabolic Research, 2022)
Bariatric surgery (BS) is the most effective therapy for severe obesity, which improves several comorbidities (such as diabetes, hypertension, dyslipidemia, among others) and results in marked weight loss. Despite these consensual beneficial effects, sleeve gastrectomy and Roux-en-Y gastric bypass (the two main bariatric techniques) have also been associated with changes in bone metabolism and progressive bone loss. The objective of this literature review is to examine the impact of bariatric surgery on bone and its main metabolic links, and to analyze the latest findings regarding the risk of fracture among patients submitted to bariatric surgery.
Keywords: bariatric surgery; bone; sleeve gastrectomy; Roux-en-Y gastric bypass; fractures